Protein folding, binding, and droplet formation in cell-like conditions. (April 2017) - Qin, Sanbo; Zhou, Huan-Xiang
Graphical abstract: Highlights: Proteins and other macromolecules weakly bind in cell-like conditions. Weak binding has many consequences, including the formation of protein droplets. Computation is positioned to accurately capture the many effects of weak binding. Abstract : The many bystander macromolecules in the crowded cellular environments present both steric repulsion and weak attraction to proteins undergoing folding or binding and hence impact the thermodynamic and kinetic properties of these processes. The weak but nonrandom binding with bystander macromolecules may facilitate subcellular localization and biological function. Weak binding also leads to the emergence of a protein-rich droplet phase, which has been implicated in regulating a variety of cellular functions. All these important problems can now be addressed by realistic modeling of intermolecular interactions. Configurational sampling of concentrated protein solutions is an ongoing challenge.